Value Pluralism and Public Ethics: Introduction. Issue 160 (1st September 2019) - Edyvane, Derek; Tillyris, Demetris
Abstract : 'The fox knows many things, but the hedgehog knows one big thing'. -Archilochus quoted in Berlin, The Hedgehog and the Fox, 22 The fragment from the Greek poet Archilochus, quoted in Isaiah Berlin's essay 'The Hedgehog and the Fox', serves as a metaphor for the long-standing contrast and rivalry between two radically different approaches to public ethics, each of which is couched in a radically different vision of the structure of moral value. On the one hand, the way of the hedgehog corresponds to the creed of value monism, reflecting a faith in the ultimate unity of the moral universe and belief in the singularity, tidiness and completeness of moral and political purposes. On the other hand, the way of the fox corresponds to the nemesis of monism, the philosophical tradition of value pluralism, to which this collection of essays is devoted. This dissenting countermovement, which emerges most clearly in the writings of Isaiah Berlin, Stuart Hampshire, Bernard Williams and John Gray, is fuelled by an appreciation of the perpetuity of plurality and conflict and, correspondingly, by the conviction that visions of moral unity and harmony are incoherent and implausible. In the view of the value pluralists, 'there is no completeness and no perfection to be found in morality' (Hampshire 1989a: 177).